Towards an equitable approach to marine plastic pollution - Vandenberg J; Yoshi O; Farrelly T (Ocean Nexus Center, University of Washington. Washington, US., 2022)
Current forms of marine plastic pollution and waste governance can, in some cases, exacerbate their inequitable burdens, and these burdens are likely to increase as plastics production continues to grow and be mismanaged. Marine plastic pollution adversely impacts humans and the environment (including food security, livelihoods, physical and mental health, and cultural practices and values), and it disproportionately impacts the lives and livelihood of more marginalized populations.